Drug Interactions in Infectious Diseases: Mechanisms and Models of Drug Interactions (Infectious Disease, 2018)
The 4th edition of Drug Interactions in Infectious Diseases is being split into two separate volumes - "Mechanisms and Models of Drug Interactions" and "Antimicrobial Drug Interactions". This volume, "Mechanisms and Models of Drug Interactions," delivers a text that enhances clinical knowledge of the complex mechanisms, risks, and consequences of drug interactions associated with antimicrobials, infection, and inflammation. The book provides a comprehensive review of basic clinical pharmacology with a focus on metabolism and transporter-mediated drug interactions. The chapters address materials that cannot be retrieved easily in the medical literature, including materials focused on the complex interrelationship of acute infection, inflammation, and the risk of drug interactions in the Drug-Cytokine chapter. The Food-Drug and Herb-Drug interactions chapters remain definitive resources. A new chapter on in vitro modeling of drug interactions is included along with updates on design and data analysis of clinical drug interaction studies. Authoritative discussion of models for regulatory decision-making on drug-drug interactions provides the necessary framework to aid antimicrobial drug development. This concise review of the mechanisms and models of drug interactions provides important insights to health care practitioners as well as scientists in drug development.